The Impact of Job Crafting Dimensions on Work Engagement Among Nurses: The mediating role of psychological capital - Mohammed Yousef Alkhraishi; Mehmet Yesiltas (ACHSM, 2024)
Work significantly influences individual well-being and human growth. Jobs are not solely formulated by companies based on their needs but are also actively modified by the individuals who hold those positions. High-stress professions, such as nursing, highlight how stress levels are influenced by factors like resource availability, patient demands, colleague interactions, and workplace cultural dynamics. Hence, this study investigates the effect of job crafting dimensions on work engagement, and examines psychological capital's mediating role in this relationship. It aims to reveal how job crafting can improve both personal and organizational well-being. This study is a descriptive cross-sectional study. The study was conducted with 348 nurses at Al Dhafra Hospitals in Abu Dhabi, UAE. The analysis utilized in this study was conducted using Structural Equation Modeling (SEM) through SmartPLS 4 and SPSS version 27 for descriptive and correlation analysis. The findings demonstrate that the impacts of job crafting dimensions-task crafting, cognitive crafting, and relational crafting-on work engagement and psychological capital are statistically significant. Additionally, the influence of psychological capital on work engagement is statistically significant. Path analysis revealed that psychological capital mediates the interaction between job crafting dimensions and work engagement. These relationships were shown to be statistically significant. This study reinforces the significance of psychological capital and job crafting dimensions as crucial attributes in the workplace. Hence, it advocates for the healthcare industry to consider the implementation of targeted programs aimed at fostering these attributes within nursing teams. Such strategic initiatives are poised to improve individual well-being among nurses, which is expected to result in enhanced organizational efficiency and a notable decrease in turnover rates over time.